Tourniquet use during total knee arthroplasty does not offer significant benefit: A retrospective cohort study. (June 2015) - Mutlu, Serhat; Guler, Olcay; Mutlu, Harun; Karaman, Ozgur; Duymus, Tahir Mutlu; Parmaksizoglu, Atilla Sancar
Abstract: Introduction: Tourniquets are routinely employed during total knee arthroplasty; however, their use remains controversial. Methods: This study investigates the efficacy and safety of this practice. A retrospective analysis of 186 patients was performed to assess benefits and/or risks associated with tourniquet use during knee arthroplasty. Total knee arthroplasty was performed using the Biomet Vanguard ® PCL Prosthesis (Biomet, Warsaw, IN, USA). In total, 126 patients who had undergone total knee arthroplasty were included in our final analysis. Results: Patients with tourniquets had significantly less intraoperative blood loss than patients without (P < .001); patients without tourniquets required more blood transfusions (P = .551), and had significantly longer surgical times (P = .011). However, patients with tourniquets had more postoperative blood loss (P < .001), longer hospital stays (P = .013), and more frequent complications (P = .571). Blood transfusion requirement was significantly associated with complications (P < .001). Conclusions: Tourniquet use provided no overall benefit. Highlights: Tourniquets are routinely employed during total knee arthroplasty; however, their use remains controversial. Thus, the routine use of tourniquets during knee arthroplasty may need to be reconsidered. Tourniquet use provided no overall benefit.